The Impact Of Shift Work On Sleep Quality And Family Life Of Saudi Nurses (The Review of Diabetic Studies, 2025)
Shift work is a common feature of nursing practice, yet it has significant implications for physiological and psychosocial well-being. This study examined the impact of shift work on sleep quality, family life, and work-family conflict among 400 Saudi nurses working in adult intensive care units and general wards across public and private hospitals. Using a cross-sectional descriptive-analytical design, data were collected via validated instruments, including the Pittsburgh Sleep Quality Index, the Work-Family Conflict Scale, and a Family Functioning Questionnaire. Results indicated that 90–96% of participants reported negative effects of shift work, with rotating and night shifts being associated with the greatest sleep disruption, family life interference, and work-family conflict. Rotating shift nurses exhibited the highest Pittsburgh Sleep Quality Index scores, greatest family disruption, and elevated work-to-family conflict. Correlation analyses revealed a strong association between poor sleep quality and work-family conflict, highlighting the interrelated nature of these outcomes. The findings underscore the need for evidence-based interventions, including optimized shift scheduling, sleep health programs, and family support initiatives, to enhance nurse well-being and promote effective work-life balance. These results have significant implications for healthcare policy, workforce planning, and quality of care in Saudi Arabia.